Explicit Feedback in Local Search Tasks - Lagun, Dmitry; Sud, Avneesh; White, Ryen W.; Bailey, Peter; Buscher, Georg (36th Annual International ACM SIGIR Conference on Research and Development in Information Retrieval (SIGIR 2013), Dublin, Ireland, 2013)
Modern search engines make extensive use of people’s contextual information to finesse result rankings. Using a searcher’s location provides an especially strong signal for adjusting results for certain classes of queries where people may have clear preference for local results, without explicitly specifying the location in the query directly. However, if the location estimate is inaccurate or searchers want to obtain many results from a particular location, they have limited control on the location focus in the search results returned. In this paper we describe a user study that examines the effect of offering searchers more control over how local preferences are gathered and used. We studied providing users with functionality to offer explicit relevance feedback (ERF) adjacent to results automatically identified as location-dependent (i.e., more from this location). They can use this functionality to indicate whether they are interested in a particular search result and desire more results from that result’s location. We compared the ERF system against a base-line (NoERF) that used the same underlying mechanisms to retrieve and rank results, but did not offer ERF support. User performance was assessed across 12 experimental participants over 12 location-sensitive topics, in a fully counter-balanced design. We found that participants interacted with ERF frequently, and there were signs that ERF has the potential to improve success rates and lead to more efficient searching for location-sensitive search tasks than NoERF.